2020
DOI: 10.1016/j.nmni.2020.100752
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunologic features among COVID-19–affected mother–infant pairs: antibodies to SARS-CoV-2 detected in breast milk

Abstract: The coronavirus disease 2019 (COVID-19) pandemic remains threatening to women and children, but clinical evidence regarding women during pregnancy, puerperium and lactation is limited. We assessed clinical and immunologic features of and breastfeeding advice provided to mother–infant pairs. This observational analysis was conducted in a tertiary-care centre in Wuhan, China. Pregnant patients with laboratory-confirmed COVID-19 who delivered during hospitalization were enrolled. Clinical characteristics and seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
2
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 17 publications
(15 reference statements)
6
46
2
14
Order By: Relevance
“…These results are supported by another study in China in 14 women in whom no SARS-CoV-2 RNA was found in breast milk, but in this study, SARS-CoV-2 antibodies (IgM or IgG) were found in only 3 samples (110). Both studies recommended that breastfeeding should continue with care in women infected with SARS-CoV-2 (109,110). Another study in China investigated the presence of SARS-CoV-2 antibodies in 64 infants, of whom 24 were born to mothers with confirmed COVID-19.…”
Section: Immunity In Special Populationssupporting
confidence: 88%
“…These results are supported by another study in China in 14 women in whom no SARS-CoV-2 RNA was found in breast milk, but in this study, SARS-CoV-2 antibodies (IgM or IgG) were found in only 3 samples (110). Both studies recommended that breastfeeding should continue with care in women infected with SARS-CoV-2 (109,110). Another study in China investigated the presence of SARS-CoV-2 antibodies in 64 infants, of whom 24 were born to mothers with confirmed COVID-19.…”
Section: Immunity In Special Populationssupporting
confidence: 88%
“…Common symptoms during pregnancy related to COVID-19 were fever, cough, sore throat, and headache. 22 Another study also observed that headache, cough, muscle aches, fever, sore throat, chills, and fatigue were the symptoms often reported during SARS-CoV-2 infection in pregnant and nonpregnant women aged between 18 and 44 years. 24 The symptoms experienced by the women who donated human milk or blood samples are likely related to mild COVID-19 infection.…”
Section: Discussionmentioning
confidence: 91%
“…17 Most studies on SARS-CoV-2 RBD-specific antibodies involve samples obtained from symptomatic patients with severe illness and hospitalization. [20][21][22] However, investigation of mild infection by SARS-CoV-2, especially breastfeeding mothers, is essential to understand their antibodies secreted in human milk. Worldwide, fever is the most frequent symptom (69.4%), followed by cough (35%), in mothers diagnosed with COVID-19 by reverse transcriptionpolymerase chain reaction (RT-PCR), whereas 13.4% of mothers with SARS-CoV-2 infection were asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…For SARS-CoV-2 the detection of viral RNA in human milk from infected women appears to be uncommon and transmission via human milk has not been recorded. Furthermore, the detection of viral RNA has only been found sporadically in samples of human milk from women infected with SARS-CoV-2 ( 14 20 ); with no milk samples showing active, replication-competent virus ( 18 ), as such, in no study has infectious virus been isolated from milk.…”
Section: Sars-cov-2 and Human Milkmentioning
confidence: 99%